Winding cell, battery pack, and vehicle
Patent Information
- Application Number
- CN202610062841.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请实施例的目的是提供一种卷绕电芯、电池包及车辆,至少解决现有防止卷绕电芯正极极片折断的贴胶方式容易造成贴胶边缘出现析锂现象,影响电池容量发挥的问题
[0015]在本申请实施例中,卷绕电芯包括:极片,极片包含正极极片和负极极片;隔膜,设置于正极极片和负极极片之间;复合胶层,至少粘贴于最内圈正极极片的拐角位置表面,其中,复合胶层绝缘且允许活性离子通过。因为复合胶层绝缘且允许活性离子通过,能够实现与正极极片粘接以改善正极极片易在拐角处折断的问题,又可以改善因粘接层带来的嵌锂不均匀、析锂、发生副反应的问题,同时提升电芯容量发挥;因此,本申请实施例所提供的卷绕电芯能够改善现有防止卷绕电芯正极极片折断的贴胶方式,容易造成贴胶边缘出现析锂现象,影响电池容量发挥的问题。
Smart Images

Figure CN123018161A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of secondary battery technology, specifically relating to a wound battery cell, a battery pack, and a vehicle. Background Technology
[0002] Currently, cell winding has become one of the main assembly methods for power batteries due to its advantages of high mechanization, high speed, guaranteed uniformity, and suitability for large-scale production.
[0003] Existing wound battery cells typically consist of a positive electrode, a negative electrode, and a separator, with the separator positioned between the positive and negative electrodes. To prevent the positive electrode from breaking, adhesive tape is often applied to its innermost side. However, due to the insulating properties of the adhesive tape, uneven lithium ion embedding occurs, leading to lithium plating at the tape's edge and affecting battery capacity. Summary of the Invention
[0004] The purpose of this application is to provide a wound battery cell, battery pack, and vehicle that at least solves the problem that existing adhesive application methods for preventing the positive electrode sheet of wound battery cells from breaking easily cause lithium plating at the adhesive edge, affecting the battery capacity.
[0005] In a first aspect, embodiments of this application provide a wound battery cell, comprising: The electrode comprises a positive electrode and a negative electrode; A diaphragm is disposed between the positive electrode and the negative electrode; A composite adhesive layer is adhered at least to the corner surface of the innermost positive electrode sheet, wherein the composite adhesive layer is insulating and allows active ions to pass through.
[0006] Optionally, in the wound battery cell, the composite adhesive layer includes a base film and an adhesive layer stacked together, and the adhesive layer is in contact with the positive electrode sheet. Both the base film and the adhesive layer have active ion transport channels, and the adhesive layer is adhesive.
[0007] Optionally, in the wound battery cell, the base film material includes at least one selected from polypropylene, polyethylene, polyethylene terephthalate, nonwoven fabric, microporous ceramics, polymer, and polyvinylidene fluoride-hexafluoropropylene copolymer; and / or, The adhesive layer is made of at least one of the following materials: acrylate adhesive, silicone adhesive, polyurethane adhesive, polyimide, and ion-conducting polymer.
[0008] Optionally, in the wound battery cell, the adhesive layer further includes nanofillers, which include at least one of ion-conducting compounds and ionophilic / wetting oxides.
[0009] Optionally, in the wound battery cell, the ion-conducting compound includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate, and lithium aluminum titanium phosphate; and / or, The ionophilic / wetting oxide includes at least one of SiO2, Al2O3, γ-AlOOH, TiO2, and ZrO2.
[0010] Optionally, in the wound battery cell, the nanofiller accounts for 5-40 wt% of the mass of the adhesive layer; and / or, The particle size D50 of the nanofiller is 20~100 nm, and the particle size D90 is less than 300 nm.
[0011] Optionally, in the wound battery cell, the thickness of the adhesive layer is 0.3~5μm; and / or, The viscosity of the adhesive layer is 20~5000 mPa·s.
[0012] Optionally, in the wound battery cell, the thickness of the composite adhesive layer is 5~15μm; and / or, The length of the composite adhesive layer along the winding direction of the positive electrode sheet is 5~20mm.
[0013] Secondly, embodiments of this application provide a secondary battery, including the wound cell described in the first aspect.
[0014] Thirdly, embodiments of this application provide a battery pack including the aforementioned wound battery cells. Fourthly, embodiments of this application provide a vehicle that includes the battery pack described in the third aspect above, the battery pack serving as a power supply for the electrical equipment.
[0015] In this embodiment, the wound cell includes: an electrode sheet comprising a positive electrode sheet and a negative electrode sheet; a separator disposed between the positive and negative electrode sheets; and a composite adhesive layer adhered at least to the corner surface of the innermost positive electrode sheet, wherein the composite adhesive layer is insulating and allows active ions to pass through. Because the composite adhesive layer is insulating and allows active ions to pass through, it can bond with the positive electrode sheet to improve the problem of the positive electrode sheet easily breaking at the corner, and can also improve the problems of uneven lithium intercalation, lithium plating, and side reactions caused by the adhesive layer, while simultaneously improving the cell's capacity. Therefore, the wound cell provided in this embodiment can improve the problem of existing adhesive application methods for preventing the positive electrode sheet of wound cells from breaking, which easily leads to lithium plating at the adhesive edge and affects the battery's capacity. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the structure of the wound battery cell provided in the embodiments of this application; Figure 2 This is a schematic diagram of the composite adhesive layer in the embodiments of this application.
[0017] Explanation of reference numerals in the attached figures: 100-Wound cell, 10-Electrode sheet, 11-Positive electrode sheet, 12-Negative electrode sheet, 20-Separator, 30-Composite adhesive layer, 31-Base film, 32-Adhesive layer. Detailed Implementation
[0018] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0019] The terms "first" and "second" in the specification and claims of this application may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise stated, "multiple" means two or more. Furthermore, "and / or" in the specification and claims indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.
[0020] A typical battery cell consists of a positive electrode, a negative electrode, and a separator, with the separator positioned between the positive and negative electrodes. In existing wound battery cells, the positive electrode is prone to breakage at corners. To prevent this, adhesive tape is often applied to the innermost side of the positive electrode. However, due to the insulating properties of the adhesive tape, uneven lithium ion insertion occurs, leading to lithium plating at the tape's edge, which affects battery capacity.
[0021] To address the aforementioned issues, this application provides a wound battery cell 100 comprising: an electrode 10, the electrode 10 including a positive electrode 11 and a negative electrode 12; a separator 20 disposed between the positive electrode 11 and the negative electrode 12; and a composite adhesive layer 30 adhered at least to the corner surface of the innermost positive electrode 11, wherein the composite adhesive layer 30 is insulating and allows active ions to pass through.
[0022] In this embodiment, because the composite adhesive layer 30 is insulating and allows active ions to pass through, it can bond with the positive electrode sheet to improve the problem of the positive electrode sheet easily breaking at the corner. It can also improve the problems of uneven lithium intercalation, lithium plating, and side reactions caused by the adhesive layer, thereby improving the cell capacity. Therefore, the wound cell provided in this embodiment can improve the problem of existing adhesive application methods that prevent the positive electrode sheet of the wound cell from breaking, which easily cause lithium plating at the adhesive edge and affect the battery capacity.
[0023] The wound battery cell provided in this application embodiment can have the active ions as lithium ions or sodium ions. That is, the wound battery cell provided in this application can be a lithium ion battery cell, or it can be a sodium ion battery cell, potassium ion battery cell, zinc ion battery cell, magnesium lithium battery cell, calcium ion battery cell, aluminum ion battery cell, etc.
[0024] Optionally, in one embodiment, the composite adhesive layer 30 is adhered at least to the inner and outer surfaces of the corner position of the innermost positive electrode 11 to better improve the overall rigidity and bending fatigue strength of the electrode at the corner, and to prevent microcracks or breakage of the aluminum foil and coating.
[0025] Optionally, in one embodiment, the composite adhesive layer 30 can also be adhered to the corner surface of other positive electrode sheets 11 to improve the overall rigidity and bending fatigue strength of the electrode sheet at the corner, and prevent microcracks or breakage of the aluminum foil and coating.
[0026] Optionally, in one embodiment, the thickness of the composite adhesive layer is 5~15μm, which can effectively balance puncture strength, notch resistance, and impedance to resist particle protrusions, edge burrs, and localized stress, as well as ensure the energy density and rate performance of the battery cell. Optionally, the thickness of the composite adhesive layer can be one or any combination of 5μm, 6μm, 8μm, 10μm, 12μm, and 15μm.
[0027] Optionally, in one embodiment, the length of the composite adhesive layer along the winding direction of the positive electrode sheet is 5-20 mm, that is, the composite adhesive layer is pasted along the winding direction of the positive electrode sheet, and the pasting length of the composite adhesive layer is 5-20 mm to completely cover the innermost easily bent part. Optionally, the width of the composite adhesive layer can be one or any combination of 5 mm, 6 mm, 8 mm, 10 mm, 15 mm, and 20 mm.
[0028] Optionally, in one embodiment, the composite adhesive layer 30 includes a base film 31 and an adhesive layer 32 stacked together, with the adhesive layer 32 in contact with the positive electrode 11. Both the base film 31 and the adhesive layer 32 have active ion transport channels, and the adhesive layer 32 is adhesive. Because the adhesive layer is adhesive and in contact with the positive electrode, and the base film and adhesive layer are stacked together, the base film and the positive electrode can be bonded together through the adhesive layer, thereby improving the overall rigidity and bending fatigue strength at the bonding point and preventing microcracks or breakage of the aluminum foil and coating. At the same time, because both the base film and the adhesive layer have active ion transport channels, the composite adhesive layer allows active ions to pass through, ensuring uniform embedding of active ions and avoiding problems such as uneven lithium embedding, lithium plating, and side reactions caused by the composite adhesive layer. The aforementioned active ion transport channels can be through-hole micropores, that is, they need to penetrate the composite coating and be continuously connected to the electrolytes on both sides.
[0029] Optionally, in one embodiment, the thickness of the adhesive layer is 0.3~5μm, which ensures continuous coverage and adhesion while avoiding excessive surface resistance caused by excessively long ion channels and microcracks or partial blockage of pores due to drying shrinkage / internal stress. Optionally, the thickness of the adhesive layer can be one or any two of the following: 0.3μm, 0.5μm, 0.8μm, 1μm, 1.5μm, 2μm, 3μm, 4μm, and 5μm.
[0030] Optionally, in one embodiment, the viscosity of the adhesive layer is 20~5000 mPa·s. This avoids the problem of adhesive material penetrating into ion transport channels and sagging, which would compromise pattern resolution and connectivity. It also ensures easy spreading, low edge buildup, and minimal formation of step defects and bubbles. Optionally, the viscosity of the coating can be any one or any two of the following: 20 mPa·s, 30 mPa·s, 50 mPa·s, 100 mPa·s, 200 mPa·s, 500 mPa·s, 1000 mPa·s, 2000 mPa·s, 21000 mPa·s, 2500 mPa·s, 3000 mPa·s, 4000 mPa·s, and 5000 mPa·s.
[0031] In some embodiments, the viscosity of the adhesive layer is 200~3000 mPa·s.
[0032] In some embodiments, the viscosity of the adhesive layer is 500~2500 mPa·s.
[0033] In this embodiment of the application, the above-mentioned composite adhesive layer can be bonded to the positive electrode sheet of the innermost ring of the wound cell by hot pressing, and the hot pressing temperature is 50~120℃.
[0034] Optionally, in one embodiment, the base film material includes at least one of polypropylene, polyethylene, polyethylene terephthalate, nonwoven fabric, microporous ceramic, polymer, and polyvinylidene fluoride-hexafluoropropylene copolymer. This base film can not only be stretched to form a base film with active ion transport channels, but also effectively improve the overall rigidity and bending fatigue strength of the positive electrode at the bonding point.
[0035] In this embodiment of the application, the base membrane material includes at least one of polypropylene, polyethylene, polyethylene terephthalate, nonwoven fabric, microporous ceramic, polymer, and polyvinylidene fluoride-hexafluoropropylene copolymer, and the base membrane has active ion transport channels, that is, the base membrane can be a diaphragm made of at least one of polypropylene, polyethylene, polyethylene terephthalate, nonwoven fabric, microporous ceramic, polymer, and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0036] Among them, the base film formed by polypropylene (PP) and polyethylene (PE) has excellent chemical stability and lithium ion permeability; the base film formed by non-woven fabric has good mechanical strength and uniform pore structure, suitable for rapid lithium ion permeation; the base film formed by polyethylene terephthalate (PET) can be compounded with other materials to increase strength and elasticity; the base film formed by microporous ceramics has excellent thermal and chemical stability; the base film formed by polymers such as PEEK is resistant to high temperature and chemical corrosion, and has high mechanical strength; while the base film prepared by the phase inversion method of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) provides better mechanical strength and thermal stability.
[0037] Optionally, in one embodiment, the adhesive layer material includes at least one of acrylate adhesive, silicone adhesive, polyurethane adhesive, polyimide, and ion-conducting polymer. The above materials not only provide the necessary adhesive function, but also do not react with other components inside the battery cell. In addition, the adhesive layer formed by the above materials is reversible, which can reduce the influence of internal stress and improve durability.
[0038] When forming the adhesive layer, the above materials can provide direct channels for active ions at the microscopic level through methods such as screen / gravure patterned coating (island / mesh gaps), laser micropores, microimprinting, micropore template transfer, or controlled phase separation to form through-hole micropores, while maintaining electronic insulation.
[0039] Among them, acrylic adhesives have good bonding properties and thermal stability, and do not react with electrolytes.
[0040] Polyurethane adhesive offers high adhesion and chemical inertness, making it suitable for long-term use in batteries.
[0041] Functionalized polyimide can impart excellent adhesive strength and high temperature resistance to the adhesive layer; optionally, the functionalized polyimide can be a polyimide (PI / PAI) system incorporating specific chemical functional groups or composite components to form a high-temperature stable, electronically insulating, electrolyte-compatible adhesive coating on the surface of the diaphragm or ceramic particles, and active ion channels are ensured through pore opening / patterning.
[0042] The ion-conducting polymer is a gel polymer electrolyte (GPE) that can be wetted / swollen by an electrolyte. It is thinly coated onto a base film that allows active ions to pass through, forming a highly active ion-conducting channel after electrolyte injection. Optionally, the aforementioned gel polymer electrolyte can be at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, acrylonitrile-methyl methacrylate copolymer, polyionic liquid / ion gel, and ceramic-filled gel polymer electrolyte.
[0043] Among them, ionic hot melt adhesives such as polyvinylidene fluoride-hexafluoropropylene copolymer / ionic liquid blends are hot-pressed and shaped after cooling, and the ionic conductivity is further improved after liquid injection.
[0044] In practical applications, the combination of base film and adhesive layer is selected according to the battery type; and the gradient function of the adhesive layer can be achieved through layered spraying, with one layer ensuring adhesion and another layer enhancing conductivity.
[0045] Optionally, in one embodiment, the base film can be a non-woven fabric, and the adhesive layer is an acrylic adhesive, which has strong adhesion and good lithium ion permeability.
[0046] Alternatively, in one embodiment, the base film can be a ceramic film, and the adhesive layer is a silicone adhesive, which enhances battery safety by improving thermal and chemical stability.
[0047] Alternatively, in one embodiment, the base film can be a polymer film, and the adhesive layer is a polyurethane adhesive. The resulting composite adhesive layer can optimize the lifespan and overall performance of the lithium-ion battery.
[0048] Optionally, in one embodiment, the adhesive layer further includes a nanofiller, which includes at least one of an ion-conducting compound and an ionophilic / wetting oxide. By introducing the above-mentioned nanofiller into the adhesive layer, it is possible to improve ion conductivity, wettability and reduce bending while maintaining electronic insulation, and at the same time improve mechanical properties and heat resistance.
[0049] Optionally, in one embodiment, the ion-conducting compound includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate, and lithium aluminum titanium phosphate.
[0050] Optionally, in one embodiment, the above-mentioned ionophilic / wetting oxide includes at least one of SiO2, Al2O3, γ-AlOOH, TiO2, and ZrO2.
[0051] Optionally, in one embodiment, the mass percentage of the aforementioned nanofiller in the adhesive layer is 5-40 wt%, which can effectively improve ion permeability while maintaining electronic insulation. Optionally, the mass percentage of the nanofiller in the adhesive layer can be one or any two of the following: 5 wt%, 6 wt%, 8 wt%, 10 wt%, 15 wt%, 20 wt%, 30 wt%, and 40 wt%.
[0052] Optionally, in one embodiment, the particle size D50 of the aforementioned nanofiller is 20~100 nm, and the particle size D90 is less than 300 nm. This particle size range ensures that the nanofiller has a high specific surface area and interfacial effect, achieving stronger interaction with the electrolyte / polymer. Simultaneously, this particle size range also ensures that its particles are smaller than the ion channel pore size, preventing "bridging" in the adhesive layer and maintaining connectivity and low tortuosity. Furthermore, this particle size range ensures that the nanofiller can be uniformly spread in the 0.3 μm~5 μm adhesive layer, with low surface roughness, reducing tip defects and dielectric weak points. Further, within this particle size range, the nanofiller can improve modulus and thermal stability, suppressing swelling / pore collapse.
[0053] Optionally, in one embodiment, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer includes a positive active material, which includes a lithium-ion transition metal oxide. The lithium-ion transition metal oxide includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, and lithium iron phosphate.
[0054] Optionally, in one embodiment, the positive electrode active material layer further includes a first conductive agent and a first binder. The first conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres. The first binder includes at least one of styrene-butadiene latex, polytetrafluoroethylene, and polyvinylidene fluoride.
[0055] In some embodiments, the positive electrode sheet is prepared as follows: the components used to prepare the positive electrode sheet, such as the positive active material including the above-mentioned positive electrode material, the first binder and the first conductive agent, are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on a second current collector such as aluminum foil; after drying, rolling, die cutting and other processes, the positive electrode sheet can be obtained.
[0056] In other embodiments, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector. The negative active material layer may be a negative active material used in batteries, and the negative active material includes any one or a combination of at least two of hard carbon, soft carbon, graphite, and silicon suboxide.
[0057] Optionally, in one embodiment, the negative electrode active material layer further includes a second conductive agent and a second binder; the second conductive agent is selected from at least one of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, and graphene; the second binder is selected from at least one of styrene-butadiene latex, polytetrafluoroethylene, and polyvinylidene fluoride.
[0058] When the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector, the negative electrode sheet is prepared as follows: The components used to prepare the negative electrode sheet, such as the negative active material, the second binder and the second conductive agent, are dispersed in a solvent such as deionized water to form a negative electrode slurry; the negative electrode slurry is coated on both sides of a negative current collector such as a copper foil; after baking, rolling, cutting and slitting, the negative electrode sheet can be obtained.
[0059] The wound battery cell provided in this application embodiment also includes an electrolyte. The positive electrode, negative electrode, and separator are stacked sequentially, and the electrolyte fills the space between the positive electrode and the separator, and between the negative electrode and the separator.
[0060] In this system, the electrolyte acts as a conductor of ions between the positive and negative electrodes. The electrolyte can be liquid, gel-like, or entirely solid. In some embodiments, a liquid electrolyte is used, comprising an electrolyte salt and a solvent, wherein the electrolyte salt is a lithium salt.
[0061] In practical applications, a composite adhesive layer is first pasted onto the corner of the innermost positive electrode sheet. Then, the negative electrode sheet, separator, and positive electrode sheet are wound together using a winding needle to obtain a core. The core is then welded and packaged to obtain a bare cell. After baking the bare cell, it undergoes liquid injection, formation, secondary sealing, and sorting to obtain the aforementioned wound cell.
[0062] This application also proposes a secondary battery, including the wound cell described in the first aspect.
[0063] This application also proposes a battery pack including a secondary battery as described above.
[0064] This application also proposes a vehicle that includes the aforementioned battery pack, which serves as a power source for the vehicle.
[0065] It should be noted that, in the embodiments of this application, the types of vehicles include, but are not limited to, pure electric vehicles and hybrid vehicles.
[0066] For the above-mentioned secondary battery, battery pack and vehicle embodiments, they include the above-mentioned wound battery cells and can achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the wound battery cell embodiments.
[0067] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0068] The present application will be described in detail below through embodiments.
[0069] Test method: (1) Initial capacity test At an ambient temperature of 25℃, the battery was charged at a constant current of 1 / 3C to the upper limit cutoff voltage (4.4 V), and then charged at a constant voltage of 0.05C. After resting for 1 hour, it was discharged at a constant current of 1 / 3C to the lower limit cutoff voltage (2.5V) to obtain the cell capacity and energy.
[0070] (2) Energy density test The ratio of cell energy to cell weight is the cell weight energy density (Wh / kg).
[0071] (3) Cyclic performance test At an ambient temperature of 25℃, charge the battery at a constant current of 1C to the upper limit cutoff voltage (4.4V), then charge at a constant voltage of 0.05C. Let it stand for 1 hour, then discharge at a constant current of 1C to the lower limit cutoff voltage (2.5V). The test ends when the capacity fading is ≤70% or after 3000 cycles.
[0072] (4) Lithium plating test: First, the charging capability of the battery cell was calibrated using a three-electrode system to obtain the charging path at 25°C. Then, the cell was charged to its upper limit cutoff voltage using this charging path. The fully charged cell was then disassembled to observe the negative electrode.
[0073] Example 1 (1) Preparation of composite adhesive layer a. A PE membrane with a thickness of 6 μm, micropores and a porosity of 40% is used as the base membrane; b. Preparation of adhesive layer coating: PVDF-HFP was stirred with a solvent to obtain a slurry with a solid content of 14 wt% and a viscosity of 580 mPa·s. The solvent was acetone / ethyl acetate (6:4).
[0074] c. Coating and drying: Gravure coating is used at a linear speed of 20 m / min to coat the PE base film to a target dry film thickness of 0.8 μm. After patterned coating and drying, an adhesive layer is formed to obtain a composite adhesive layer.
[0075] (2) Preparation of positive electrode sheet NCM622, conductive carbon black (SP), and PVDF were mixed in a weight ratio of approximately 96:2:2 in the solvent N-methylpyrrolidone and stirred until homogeneous to obtain a positive electrode slurry. The positive electrode slurry was then coated on both sides of an aluminum foil for current collectors. A 10 mm wide flexible insulating coating was then applied to the edge of the positive electrode slurry. The mixture was baked at 120°C for 1 h and subsequently cold-pressed, cut, and slit to obtain the positive electrode sheet.
[0076] (3) Preparation of negative electrode sheet Artificial graphite was mixed evenly with conductive agent SuperP, conductive agent CNT, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber latex (SBR) in a mass ratio of 95.64:1:0.06:1.3:2 to prepare a lithium-ion battery negative electrode slurry. The slurry was then coated on both sides of a copper foil for current collectors, and after baking, rolling, and cutting, the negative electrode sheet was obtained.
[0077] (4) Assemble bare cells By using an adhesive layer to contact the positive electrode sheet, a composite adhesive layer is applied to the inner corner of the positive electrode sheet, covering a length of 6 mm. The layers are then hot-pressed together at 90°C. The positive electrode, separator, and negative electrode are then stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The layers are then wound up, and a finishing adhesive tape is applied at the winding point to obtain the bare battery cell.
[0078] (5) Preparation of electrolyte Ethylene carbonate and methyl ethyl carbonate were mixed at a mass ratio of 3:7 to obtain a solvent, and then lithium hexafluorophosphate was added at a concentration of 1.0 mol / L to obtain an electrolyte.
[0079] (6) Battery preparation The bare battery cell is placed into an aluminum shell, dried at 100°C, and then injected with the prepared electrolyte. After vacuum sealing, settling, formation, and shaping, the lithium-ion battery is completed.
[0080] Comparative Example 1 The only difference from Example 1 is that step (1) is omitted, and in the step of assembling the bare battery cell, the composite adhesive layer is replaced with ordinary ion-insulating adhesive paper.
[0081] Initial capacity, energy density, and cycle performance tests were performed on the lithium-ion batteries in each test case (including the examples and comparative examples), and the results are shown in Table 1.
[0082] Table 1
[0083] In summary, in this embodiment, the wound cell includes: an electrode sheet comprising a positive electrode sheet and a negative electrode sheet; a separator disposed between the positive and negative electrode sheets; and a composite adhesive layer adhered at least to the corner surface of the innermost positive electrode sheet, wherein the composite adhesive layer is insulating and allows active ions to pass through. Because the composite adhesive layer is insulating and allows active ions to pass through, it can bond with the positive electrode sheet to improve the problem of the positive electrode sheet easily breaking at the corner, and can also improve the problems of uneven lithium intercalation, lithium plating, and side reactions caused by the adhesive layer, thereby improving the cell capacity. Therefore, the wound cell provided in this embodiment can improve the problem of existing adhesive application methods for preventing the positive electrode sheet from breaking, which easily leads to lithium plating at the adhesive edge and affects the battery capacity.
[0084] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0085] The foregoing has provided a detailed description of a wound battery cell, battery pack, and vehicle provided by this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A wound battery cell, characterized in that, include: The electrode comprises a positive electrode and a negative electrode; A diaphragm is disposed between the positive electrode and the negative electrode; A composite adhesive layer is adhered at least to the corner surface of the innermost positive electrode sheet, wherein the composite adhesive layer is insulating and allows active ions to pass through.
2. The wound battery cell according to claim 1, characterized in that, The composite adhesive layer includes a base film and an adhesive layer stacked together, and the adhesive layer is in contact with the positive electrode sheet. Both the base film and the adhesive layer have active ion transport channels, and the adhesive layer is adhesive.
3. The wound battery cell according to claim 2, characterized in that, The base film is made of at least one of the following materials: polypropylene, polyethylene, polyethylene terephthalate, nonwoven fabric, microporous ceramics, polymer, and polyvinylidene fluoride-hexafluoropropylene copolymer; and / or The adhesive layer is made of at least one of the following materials: acrylate adhesive, silicone adhesive, polyurethane adhesive, polyimide, and ion-conducting polymer.
4. The wound battery cell according to claim 2 or 3, characterized in that, The adhesive layer further includes nanofillers, which include at least one of ion-conducting compounds and ionophilic / wetting oxides.
5. The wound battery cell according to claim 4, characterized in that, The ion-conducting compound includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium aluminum germanium phosphate; and / or, The ionophilic / wetting oxide includes at least one of SiO2, Al2O3, γ-AlOOH, TiO2, and ZrO2.
6. The wound battery cell according to claim 4 or 5, characterized in that, The nanofiller comprises 5-40 wt% of the adhesive layer by mass; and / or, The particle size D50 of the nanofiller is 20~100 nm, and the particle size D90 is less than 300 nm.
7. The wound battery cell according to any one of claims 2 to 6, characterized in that, The thickness of the adhesive layer is 0.3~5μm; and / or, The viscosity of the adhesive layer is 20~5000 mPa·s.
8. The wound battery cell according to any one of claims 1 to 7, characterized in that, The thickness of the composite adhesive layer is 5~15μm; and / or, The length of the composite adhesive layer along the winding direction of the positive electrode sheet is 5~20mm.
9. A battery pack, characterized in that, Includes wound cells as described in any one of claims 1 to 8.
10. A vehicle, characterized in that, Includes the battery pack as described in claim 9, wherein the battery pack serves as a power supply for the vehicle.
